A rare case of congenital vitiligo in a neonate with a review of literature - Debasmita Behera; Farheen Begum; Chinmoy Raj; Garima Manocha (Pigment International)
Congenital vitiligo is a very rare entity, but cases in infancy have been reported. We are presenting the case of a 2-month-old male infant who came to us with complaints of multiple progressive white patches over the body since birth. The lesions showed white accentuation with fluorescence under a Wood’s lamp. There was a positive history of vitiligo in the maternal grandmother. The infant was successfully treated with topical pimecrolimus 1% cream. Our case in point contributes to the limited pool of studies on congenital vitiligo (nine cases reported till date) and lends credibility to the theory that, in genetically vulnerable individuals, the autoimmune process may begin in utero.